Telemedizin in der Rheumatologie - Krusche, M.; Mühlensiepen, F.; Aries, P.; Welcker, M.; Knitza, Johannes (Zeitschrift für Rheumatologie, 2020)
Due to the outbreak of the COVID-19 pandemic, in recent months we have experienced deep changes in our daily and professional lives. In the context of pandemic containment, routine rheumatological procedures have changed in many areas. To guarantee sufficient protection against the infection for patients and staff, telemedicine (especially telephone and video consultation) has increasingly been used. Due to the Digital Healthcare Act (DiGAV), whereby patients will have a legal claim to specific digital health applications in Germany, medical apps and wearables will offer new opportunities for telemedical monitoring. This article provides an overview of telemedical care options in the field of rheumatology. Furthermore, opportunities and limitations of telemedicine in rheumatology are reviewed.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Apps; Digitalization; Telephone consultation; Video consultation; Wearables